Megagametophyte development and female sterility in Maytenus obtusifolia Mart. (Celastraceae) - Nader Haddad, Isabella Verissimo; Sa-Haiad, Barbara de; Ribeiro de Santiago-Fernandes, Lygia Dolores; Machado, Silvia Rodrigues [UNESP] (Springer, 2019)
Reproduction in flowering plants is closely related to the megagametophyte, since the megagametophyte is involved in pollen tube reception and contains the two female gametes-egg cell and central cell. Previous conventional light microscopy methods have shown that female sterility in perfect flowers of Maytenus obtusifolia is associated with the occurrence of sterile ovules whose megagametophytes have hypertrophied synergids. Here, using transmission electron microscopy and cytochemical methods, we compare the megagametophytes in fertile and sterile ovules from perfect and pistillate flowers, and investigate the cellular events that result in the degradation of the megagametophyte cells from sterile ovules. In fertile ovules of perfect and pistillate flowers, mature megagametophytes have two synergids, egg cell and central cell. In fertile ovules, the synergids present an extensive rough endoplasmic reticulum (RER) profile, large populations of mitochondria, when compared to egg cells, vesicles, Golgi bodies, plastids and a nucleus with heterochromatin. Besides that, the egg cell has a small population of organelles and the central cell exhibits cytoplasm with free ribosomes, RER, vesicles originating from the RER, Golgi bodies and oil inclusions. In mature megagametophytes from sterile ovules of perfect and pistillate flowers, massive autophagy occurs by tonoplast rupture promoting hydrolase release, leading to protoplast and cell wall degradation-typical evidence of programmed cell death (PCD). Therefore, female sterility in the majority of M. obtusifolia sterile ovules is the result of PCD by massive autophagy in the megagametophyte cells. In a few other sterile ovules, sterility is due to the delayed or the absence of megagametophyte development.
Keywords: Autophagy; Cytochemistry; Programmed cell death (PCD); Ultrastructure; Vacuolar cell death